CHILDREN’S LITERATURE OF MINANGKABAU IN CHARACTER BUILDING OF THE NATION GENERATION - Khairil Anwar (International Conference on Languages and Arts, 2014)
Children’s literature is a literary works consumed and/or produced by children in their inter-action to the environment. This kind of literature tends to be marginalized in academic, productivity and the use of the literature itself. Compared to children’s literature of other regions existing in Minangkabau territory seems almost forgotten. Children’s literature contains ideology of the author and his collectivity which is unconsciously easy and straight will be absorbed by the children, and it will influence their character, for example, they want to become a figure of hero from the comics or story they read. So easy are the children absorbed in the story they read, therefore, we need and idea to offer and serve children literature texts containing local character, particularly Minangkabau, and generally Indonesia so that they do not go off their Indonesian root. The discussion on the children literature becomes urgent. Any children literature of Minangkabau having become tradition, how the production, and the use of them for children’s world must paid attention on. The children’s literature of Minangkabau may be said available in oral form, and may be covered in punning when they are inter-acting to the environment. The creation and production are quite saddening. Meanwhile the use of it tends to be marginalized either in daily life or in education. From academic point of view there is so little making use of it as a material of study as well as from production view pint there not many children’s literature born in comparison to adult’s, or juvenile’s one. Let alone the use of it, the children tend to consume the imported one for they are more various, and packed more interestingly. In fact, the children literature may put on the foundation to form characterized national generation based on creativity, plurality tolerance.   Keywords: ideology, character, marginal, and children’s literature.